Voicing the Silenced: Female Agency and Resistance in Ratna Sarumpaet's Marsinah Menggugat - Julianti Hairani Srg; Rahmawati Rahmawati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study explores female agency and resistance as central dramatic elements in Ratna Sarumpaet’s political play Marsinah Menggugat (1994). Set during Indonesia’s New Order regime under Suharto’s leadership, the play portrays the murder of labor activist Marsinah and presents her ghost as an accuser seeking justice and challenging historical silence. Drawing on feminist theatre theory, postcolonial discourse, and the concept of subaltern agency, this study argues that Sarumpaet represents Marsinah not merely as a victim of oppression but as a powerful female figure who resists the erasure imposed by state authority and patriarchal structures. Employing a qualitative research approach based on feminist literary criticism, the study uses the play script as the primary data source. Data analysis involves close reading, thematic categorization, and interpretive analysis through the perspectives of Diamond (1997), Butler (1990), Spivak (1988), and Suryakusuma (1996). The findings reveal four forms of female agency: the monologue as an expression of an autonomous female voice, the spectral body as a symbol of political resistance, language and naming as acts against state-imposed silence, and personal testimony as a foundation for collective feminist solidarity. This study demonstrates that Marsinah Menggugat transforms theatre into a counter-hegemonic space where marginalized women reclaim historical narratives, challenge authoritarian power, and preserve collective memory through performance and resistance.